KEDUDUKAN PERJANJIAN WALI AMANAT TERHADAP LEGAL STANDING PEMEGANG EFEK BERSIFAT UTANG (CONTOH KASUS PUTUSAN NOMOR: 121/PDT.SUS-PKPU/2018/PN JKT.PST) - Kevin Neil McVey; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2019)
A legal concept of trust, or also known as ‘wali amanat’ in Indonesian legal terms, is not a really well-known concept amongst the legal practitioner and jurist in the Indonesian court. The concept has been a topic of hot debate between lawyers and judges on whether the concept is applicable in the realm of the Indonesian European-Continental law system. The problem arises from a case of debt restructuring, in the commercial court decision No: 121/Pdt.sus-PKPU/2018/PN.Jkt.Pst. The decision carries that a bond-holder could file an application for debt restructuring (PKPU) when they see a case of default on the bond issuer. The bond-holders are supposed to be bound to the trust indenture, and the indenture already stipulated in its term on who has the legal power and authority to do so. The stipulation turns out to be the complete opposite of what’s reflected in the court decision, making the epicenter of the problem revolves on whether the underling bond-holders has the capability to file a debt restructuring application. This essay aims to analyze the decision and determines who has the authority and legal standing to file a debt restructuring application in the case when a trust indenture exists.